THE MESSAGE DESIGN IN ARABIC LEARNING INTEGRATED WITH CHARACTER BUILDING (Applied in Reading Skill for Rasionally Level) - Machmudah, Umi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Nowadays, there are some negative phenomenon related to the attitude, such as the children that become far away from the Islamic value. There are some causes of the phenomenon, namely poverty, divorce, spouse conflict in a family, the absence of the parents role in children’s education, inappropriate society, and immoral friends. These bad things could be restrained by using learning because learning is a certain condition where there are interaction between a giver, which is the teacher, and a receiver, which is the student. In this interaction, the teacher, using certain condition and purpose, helps student to get knowledge, guidance, skill, and value that can straighten an attitude. Among the message is moral value. The students’ development could also be improved by character value. Arabic learning has a purpose to give student language skill, and its components. By Arabic learning, it is also possible to give students moral value. One of the factors to make successful learning is the available of learning sources, which are people, material, device, hardware, technique, message, and setting. Message is the main of a learning that are given by the teacher. The objectives of the paper is to 1) describes the message design in Arabic learning (reading skill) that is integrated with character building (according to the message types, design characteristic, form of the design, language skill, character building types, learning method used in character building), 2) describes the form of the message design principle. The methodology used in this paper is qualitative description using literature studies type with qualitative analysis. The findings are 1) the material of reading, that the character of the message design is static, the form of the design is by replacing the antonym of the underlined word, the message is the value, the character taught is religious character ( birrul walidain , and responsibility), and the character building method is giving advice or lecturing. 2) The application of the message design principles are; 1) readiness and motivation: the existence of an instruction, and the title of the text, 2) attention directing device: the existence of an underline in the word, 3) student’s active participation: replacing the antonym of the underlined word, 4) repetition: getting more replacing word, 5) feedback: the teacher correction and appreciation.